Knowledge translation in times of the COVID-19 pandemic in quilombola community - Nunes Moraes-Partelli, Adriana; Amabiles Pazini, José Marcos; Pestana Santos, Aline; Lorencini Santos, Isabela; Pereira Coelho, Marta (Guará Journal, 2023)
OBJECTIVE: To illustrate the translation of knowledge in the format of educational health material carried out in times of a pandemic for quilombola community. METHODOLOGY: Qualita-tive and bibliographic study, developed in the following stages: 1) Survey of scientific content on COVID-19 through bibliographic research; 2) Production of a booklet with information on conta-gion, dissemination and how to prevent COVID-19 in the quilom-bola community, considering the rgoup with ancestors from the African continent.; and 3) Delivery of the booklet to the Municipal Health Department for distribution to the Health Units that have quilombola communities in their territory. RESULTS: The literatu-re review contributed scientifically to the survey of themes for the composition of the booklet. Afterwards, a storyboard was crea-ted where the illustrations, the textual content and the language used were defined. A company was hired that illustrated and dia-grammed the final product: “Quilombola community in focus: on preventing the contagion and spread of the Coronavirus”. The de-livery of 680 printed copies of the booklet was made to the Muni-cipal Health Department of São Mateus. CONCLUSION: This study was developed by applying the university pillar (teaching-resear-ch-extension), which directly impacted the training of undergra-duate students and culminated in the production of educational technology containing content with an urgent and current social problem, contributing to the inclusion of social groups in a situa-tion of vulnerability.